Research on Novel CMUTs for Detecting Micro-Pressure with Ultra-High Sensitivity and Linearity - Ding, Qi; Wang, Hongliang; Zhang, Hanqiang; Huang, Xiao; Sun, Xiaolei; Qin, Zhenjie; Ren, Rui; Zhu, Jiajun; He, Changde; Zhang, Wendong (Micromachines (Basel), 2021)
Capacitive micromachined ultrasonic transducers (CMUTs) have been indispensable owing to their resonance characteristics in the MHz frequency range. However, the inferior pressure sensitivity and linearity of traditional CMUTs themselves cannot meet the actual demands of micro-pressure measurements. In this paper, two novel CMUTs are proposed for the first time to improve the measuring performance of micro-pressure in the range of 0–10 kPa. The core concept of the enhancement is strengthening membrane deformability by partly adjusting the CMUT framework under the combined action of electrostatic force and uniform pressure. Two modified structures of an inverted frustum cone-like cavity and slotted membrane are presented, respectively, and a finite element model (FEM) of CMUT was constructed and analyzed using COMSOL Multiphysics 5.5. The results demonstrate that the maximum displacement and pressure sensitivity are improved by 16.01% and 30.79% for the frustum cone-like cavity and 104.22% and 1861.31% for the slotted membrane, respectively. Furthermore, the results show that the width uniformity of the grooves does not influence the characteristics of the membrane, which mainly depend on the total width of the grooves, greatly enriching design flexibility. In brief, the proposed structural designs can significantly improve the micro-pressure measurement performance of the CMUT, which will accelerate the rapid breakthrough of technical barriers in the fields of aerospace, industry control, and other sensing domains.